Vibration Characteristics of the Bearing Rotor Shaft - Baher, Karrar; Atiyah, Qasim A.; Abdulsahib, Imad A. (Al-Nahrain Journal for Engineering Sciences, 2022)
In this work, the vibrations in the rotor-bearing system are studied experimentally and theoretically using ANSYS Workbench 2020 R1 software to compute the natural frequencies and mode shapes. In the experimental part, the LABVIEW software was used to examine the signal of the frequency domain values obtained from the accelerometer sensors, based on Fast Fourier Transform (FFT) technology and dynamic response spectrum. in the theoretical part, the natural frequencies are determined based on the finite element method for analyzing the system and knowing its behavior and vibration response level. The results showed that the level of vibration becomes higher at high rotational speeds, and it becomes large when the distances between the bearings are large, according to the bearing position and type used in the system. in this work can be concluded, the system is usually affected by the dynamic response around it and is difficult to separate from it, and the vibrations in the system can be controlled by adding an external damping source, which gives the system more stable. A system operating at high speeds can give a large vibration and an unbalanced response.